Spirit untamed [videorecording (DVD)] (Universal Pictures Home Entertainment, 2021)
Free-spirited Lucky Prescott moves to Miradero to join her estranged father, and is decidedly unimpressed with the sleepy town until she discovers a unique tie to her late mother, who was a fearless horse-riding stunt performer. She quickly forms a bond with a wild mustang named Spirit and makes two new pals who love horses as much as she does. When a heartless wrangler plans to capture Spirit and his herd, Lucky and her friends set off on an epic journey to rescue the horse who has given her an unbreakable connection to her mother's legacy.